CARDIAC SURGERYThe impact of coronary artery disease severity on late survival after combined aortic valve replacement and coronary artery bypass grafting – experience of a single cardiac surgery center - Perek, Bartłomiej; Misterski, Marcin; Stachowiak, Wojciech; Buczkowski, Piotr; Stefaniak, Sebastian; Puślecki, Mateusz; Urbanowicz, Tomasz; Budniak, Wiktor; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: The severity of coronary artery disease (CAD) may have an impact on the outcomes of patients (pts) after aortic valve replacement (AVR) and coronary artery bypass grafting (CABG). Aim : The aim of the study was to analyze survival after simultaneous AVR and CABG with respect to CAD severity. Material and methods : The study involved 143 consecutive pts (40 women and 103 men) with a mean age of 65.1 ± 7.7 years treated between 2006 and 2009. The indication for surgery was aortic stenosis accompanied by left main or three-vessel disease (group A; n = 43) and by single- or two-vessel disease (group B; n = 100). In-hospital and late mortality were analyzed. Post-discharge survival was estimated using the Kaplan-Meier method. Moreover, selected preoperative clinical and echocardiographic data as well as intraoperative variables were compared between the groups. Results : In-hospital mortality was 4.7% in group A and 3.0% in group B (NS). The 12-month and 48-month survival probability rates were 0.88 ± 0.05 and 0.83 ± 0.06 in group A, and 0.97 ± 0.01 and 0.92 ± 0.03 in group B, respectively (p < 0.05). Patients in group A and B differed (p < 0.05) with respect to the preoperative prevalence of arterial hypertension (65.1% vs. 42.0%) and atrial fibrillation (18.6% vs. 6.0%) as well as with regard to the rate of complete revascularization (20.9% vs. 85.0%, group A and B, respectively). Conclusions : Coronary artery disease severity impacts long-term survival after combined AVR and CABG. Patients with left main or three-vessel disease more often undergo incomplete surgical revascularization, and this fact may be one of the predictors of an unfavorable outcome.